JUDICIAL REVIEW IN SOUTH AFRICA AND INDIA: ADVANCING CONSTITUTIONALISM OR UNDUE ACTIVISM? - Radley Henrico (Obiter, 2023)
The Supreme Court of India and the Constitutional Court of South Africa, as apex courts, also function as guardians of the constitutions of each respective country. This article seeks to establish the extent to which judicial review in India and South Africa can be said to be more aligned with constitutionalism or undue activism. An assessment of the aforesaid is determined with regard to the transformative and progressive constitutional interpretation approach adopted by the aforesaid courts which also gives impetus to the living tree doctrine, the role that dignity plays in giving substantive meaning to democracy, ineptitude, and or corruption on the part of the executive precluding the effective realisation of socio-economic rights as well as parliament’s failure to hold members of the executive to account. The extent to which constitutionalism, as opposed to undue activism, has been advanced by the aforesaid courts is demonstrated with reference to specific cases.